Pilot study of a customized nanotextile wet garment treatment on moderate and severe atopic dermatitis: A randomized clinical trial. Issue 1 (30th October 2019) - He, Huiling; Koh, Mark Jean‐Aan; Lee, Haur Yueh; Ang, Seng Bin
Abstract: Background: Atopic dermatitis (AD) is a common dermatosis. The cornerstone of eczema management is to repair and maintain skin barrier and hydration, as well as to reduce inflammation. Wet wrap therapy (WWT) is a widely used adjunct to achieve this. The conventional material used for WWT is viscose, which presents drawbacks including discomfort, high cost, and poor durability. Here, we explore the possibility of using customized nanotextile (nanopolyester) for WWT, hoping to prove that this material is non‐inferior to viscose in clinical effectiveness and patient acceptance. Methods: Patients aged 0‐18 years with moderate to severe eczema were randomized to receive either viscose (Tubifast™) or nanotextile for WWT. Patients were instructed to apply WWT daily overnight for 2 weeks. Patients' disease severity score (IGA, SCORAD) and quality of life (QoL) score (IDQOL/CDLQI) were measured on day 0, 7, and 14 of treatment. Patient survey was conducted to collect patients' feedback about garment use. Results: Fifty‐three children aged 7 months to 17 years were recruited (27 in Tubifast™ and 26 in nanotextile group). Patients in both groups showed significant improvement in disease severity and QoL from baseline ( P < .001), and such improvement was similar in both groups. However, nanotextile garment was significantly more comfortable (2.73/10 vs 5.12/10, P = .001), easier to wear (2.78/10 vs 5.24/10, P = .003), and cooler (2.43/10 vs 3.96/10, P = .033) from patients' feedback. Conclusion: This study demonstrates that nanomaterial is as effective as conventional viscose in WWT, while superior in patient acceptability. Nanotextile for WWT has good potential in eczema management, especially in patients with suboptimal response to topicals alone.